Dalle risorse al know how esclusivo: il ruolo della corporate governance nello sviluppo di un’impresa familiare - Di Toma, Paolo (Piccola Impresa / Small Business, 2012)
Although an increasing amount of literature has identified the role of dynamic capabilities as a source of competitive advantage, we still have little knowledge as to how corporate governance may influence their development. This paper addresses how corporate governance practices may be strategically employed to change the firm’s resources and create new knowledge which enables the development of dynamic capabilities in a family firm. Our data show how value creation may result not merely from the possession of unique resources, but from how family members perform their day to day practice of strategy by managing resources which may enable the achievement of dynamic capabilities.